Mechanical Performance Investigation of a Flat-Roof and Four-Slope Folded Plate Structure - Yan Yang; Meng Zhan; Yanfei Huang (Advances in Civil Engineering)
The flat-roof and four-slope folded plate structure is a space thin-walled structure composed of four trapezoidal plates and a rectangular plate parallel to the bottom surface, which is widely used in various engineering applications. In order to clarify the force transmission path and stress distribution law under the action of this structural load, the folded plate structures were made by utilizing the plexiglass with the thicknesses of 3 and 4 mm, respectively, and had the simple support on opposite sides and fixed support on another opposite side. Then, the static load tests and ANSYS finite element analysis were implemented, and the results were compared. It shows that the test results are basically consistent with the finite element calculation results, the maximum stress values of the folded plate structure along the X and Y directions appear in the same position, and the maximum stress value of a 3 mm thick folded plate structure is greater than that of 4 mm. The junction position of the roof and the slope plate is the dangerous section, and the special treatment should be made for this section to prevent the damage of folded plate structure in the practical engineering. Moreover, some reasonable measures also should be taken to meet the design requirements of the plate–plate junction position.